2023
DOI: 10.1007/s10393-023-01647-6
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Drought on HIV Care in Rural South Africa: An Interrupted Time Series Analysis

Abstract: This analysis investigates the relationship between drought and antiretroviral treatment (ART) adherence and retention in HIV care in the Hlabisa sub-district, KwaZulu-Natal, South Africa. Data on drought and ART adherence and retention were collated for the study period 2010–2019. Drought was quantified using the 3-month Standard Precipitation Evapotranspiration Index (SPEI) and Standard Precipitation Index (SPI) from station data. Adherence, proxied by the Medication Possession Ratio (MPR), and retention dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Otherwise, previous cross-sectional studies of weather and HIV in sub-Saharan Africa have found associations between local rainfall shocks and heightened HIV prevalence [ 25 ], as well as between drought and increased HIV prevalence and riskier sexual behaviour in young women in rural areas [ 26 ]. A recent study in South Africa found that adherence and retention in care decreased during years of drought [ 14 ]. Another study found evidence that unusually heavy rainfall was associated with a higher HIV burden across 21 sub-Saharan African countries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, previous cross-sectional studies of weather and HIV in sub-Saharan Africa have found associations between local rainfall shocks and heightened HIV prevalence [ 25 ], as well as between drought and increased HIV prevalence and riskier sexual behaviour in young women in rural areas [ 26 ]. A recent study in South Africa found that adherence and retention in care decreased during years of drought [ 14 ]. Another study found evidence that unusually heavy rainfall was associated with a higher HIV burden across 21 sub-Saharan African countries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…That much of this literature found associations between droughts and HIV-related outcomes among women living in rural areas show both the gender and urban/rural divides in the pathways linking drought and HIV. Studies suggest that the impacts of climate on HIV are seen particularly among women because of greater dependence on transactional sex [ 30 ], and that the effects are concentrated in rural areas, due to changes in climate having very direct impacts on the livelihoods and behaviours of farmers, whilst any affects in urban areas would likely be less direct, potentially occurring through drought affecting the general economy [ 14 ]. Other literature has looked at the effects of drought in sub-Saharan Africa on other health outcomes that, like HIV, would be more indirectly affected by climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation